Implementation of the new public management in Costa Rica: The case of the application, replacement and renewal of passports in the offices of the Bank of Costa Rica (2007-2014) - Díaz González, José Andrés (2016)
This paper discusses about the implementation of a reform in the process of passport renewal and replacement in Costa Rica. This reform is consistent with the indications given by the new public management in order to improve the effi-ciency of services provided by the public administration. It is concluded that the reform was successfully implemented, due to two factors: first, it was designed to meet the needs of service users; and second, it counted on high-level political support, which facilitated the required coordination for service implementation between the involved institutions.